2018
DOI: 10.1177/0891243218786686
|View full text |Cite
|
Sign up to set email alerts
|

The Making of a Human Rights Issue: A Cross-National Analysis of Gender-Based Violence in Textbooks, 1950-2011

Abstract: In the past few decades, awareness around gender-based violence (GBV) has expanded on a global scale with increased attention in global treaties, organizations, and conferences. Previously a taboo topic, it is now viewed as a human rights violation in the broader world culture. Drawing on a quantitative analysis of 568 textbooks from 76 countries from across the world, we examine the extent to which this growing global attention to GBV has filtered down into national educational curricula. We find that textboo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The interventions identified in this review have been shown to be effective in overcoming gender stereotypes. Research has shown how stereotypes hinder gender equality and can encourage violent behavior [38][39][40]. Therefore, raising awareness against gender stereotypes is a step in the prevention of gender-based violence.…”
Section: Discussionmentioning
confidence: 99%
“…The interventions identified in this review have been shown to be effective in overcoming gender stereotypes. Research has shown how stereotypes hinder gender equality and can encourage violent behavior [38][39][40]. Therefore, raising awareness against gender stereotypes is a step in the prevention of gender-based violence.…”
Section: Discussionmentioning
confidence: 99%
“…International women's rights are not unequivocally defined, however, and leave room for different interpretations and contestations, so it is expected that progressive social policies and norm cascades can only go so far without provoking a pendulum swing response from the resulting conflict over changing gender norms (Stewart 2010;Sikkink 2011). It is unfortunate that normspoiling tactics are then used to delegitimize human rights and zero-tolerance policies toward gender-based abuse and violence against vulnerable minority groups who are perceived to challenge traditional marriage and family norms (Sanders 2018;Russell et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Linkages to international organizations represent a proxy for such connections, with memberships in these organizations serving as ‘receptor site’ for global ideas (Boli and Thomas, 1997; Lerch, 2019). Several curriculum studies document greater uptakes of world cultural models in countries that are more embedded in the global institutional environment (Bromley et al, 2011; Russell et al, 2018). We expect similar dynamics to lead to national variations in our case.…”
Section: Arguments and Hypothesesmentioning
confidence: 99%